2023
DOI: 10.1055/s-0043-1761294
|View full text |Cite
|
Sign up to set email alerts
|

Low serum uric acid levels and levodopa-induced dyskinesia in Parkinson's disease

Abstract: Background Levodopa is the most used and effective medication for motor symptoms of Parkinson disease (PD), its long-term use is associated with the appearance of levodopa-induced dyskinesia (LID). Uric acid (UA) is believed to play an important neuroprotective role in PD. Objective To investigate if serum UA levels are related with the presence of LIDs in PD patients. Also, we investigated the associations among UA levels and clinical features of PD. Methods We enrolled 81 PD patients (dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Moreover, a low circulating level of UA may have an association with the severity of PD's clinical presentations as one study revealed that low UA may correlate with dyskinesia severity, especially in women 29 . Moreover, some risk factors of PD such as underlying genetic mutations may be associated with UA metabolism and may affect its serum level in one study, the underlying LRRK2 mutation may associate with a lower level of UA than idiopathic PD 30 …”
Section: Discussionmentioning
confidence: 98%
“…Moreover, a low circulating level of UA may have an association with the severity of PD's clinical presentations as one study revealed that low UA may correlate with dyskinesia severity, especially in women 29 . Moreover, some risk factors of PD such as underlying genetic mutations may be associated with UA metabolism and may affect its serum level in one study, the underlying LRRK2 mutation may associate with a lower level of UA than idiopathic PD 30 …”
Section: Discussionmentioning
confidence: 98%
“…For example, CSF biomarkers including alpha-synuclein (α-Syn), amyloid β1-42 (Aβ 42 ), total tau (t-tau), and phosphorylated tau (p-tau) are associated with cognitive decline and can serve as independent predictors of cognitive impairment in PD [13]. Low levels of uric acid are significantly correlated with motor impairments [14]. Genetic factors have also played a significant role in PD, although less than 1% of cases are caused by a single gene mutation [2].…”
Section: Introductionmentioning
confidence: 99%